Breast carcinoma with osteoclastic giant cells: case report and review of the literature - Niu, Ya (e-Century Publishing Corporation, 2014)
Breast carcinoma with osteoclastic giant cells (OGCs) are uncommon. Here, we report a 46-year-old woman with a painless lump in her left breast that has been proved clinically and radiographically. Microscopical examination showed OGCs accompanying invasive ductal carcinoma. Immunohistochemical assay revealed that OGCs derived from macrophages. Despite positive lymph node metastasis, the patient has been well without evidence of recurrence or metastasis one year after the operation. To date, the influence of OGCs on the prognosis of patients is still controversial. Our case may provide insights into further understanding beast carcinoma with OGCs.